Response to Comment on “Planetary boundaries: Guiding human development on a changing planet” - Gerten, Dieter; Rockström, Johan; Heinke, Jens; Steffen, Will; Richardson, Katherine; Cornell, Sarah (American Association for the Advancement of Science, 2015)
Jaramillo and Destouni claim that freshwater consumption is beyond the planetary boundary, based on high estimates of water cycle components, different definitions of water consumption, and extrapolation from a single case study. The difference from our analysis, based on mainstream assessments of global water consumption, highlights the need for clearer definitions of water cycle components and improved models and databases.